Fulminant Hepatic Failure Due to Dengue - Sedhain, A; Adhikari, S; Regmi, S; Chaudhari, S K; Shah, M; Shrestha, B (Kathmandu University Medical Journal, 2012)
Dengue Fever (DF) is only rarely considered as a cause of acute liver failure even globally and only a few case reports of acute hepatic failure and encephalopathy occurring in DF in adults are available. We report a case of Acute Liver Failure due to Dengue during a major outbreak in 2010 in Chitwan. A 20 year old previously healthy female presented to the emergency department of Chitwan Medical College with fever, jaundice and altered sensorium. She was tested positive for Dengue IgM. Her biochemical and clinical parameters were suggestive of acute liver failure with total billirubin of 10.1 mg/dL, direct billirubin of 5.2 mg/dL, ALT 5760 IU, AST 14100 IU, alkaline phosphatase of 1250 IU, PT INR of 1.76 and platelet count of 30,000 /mm3. Other causes for acute hepatic failure like acute viral hepatitis, leptospirosis, malaria, Reye’s syndrome were ruled out. The patient was admitted and managed in the ICU with supportive care and platelet transfusion. With treatment she made a significant clinical and biochemical improvement with AST of 105 IU, ALT of 120 IU and platelet count of 150,000/mm3. She was discharged after 11 days of hospital stay.DOI: http://dx.doi.org/10.3126/kumj.v9i2.6293 Kathmandu Univ Med J 2011;9(2):73-5